2010
DOI: 10.1063/1.3498818
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of recombination at the surface and in the substrate on carrier lifetimes of n-type 4H–SiC epilayers

Abstract: After remarkable reduction in the Z1/2 center in n-type 4H–SiC epilayers, the measured carrier lifetimes can be severely affected by other recombination paths. Impacts of carrier recombination at the surface as well as in the substrate are investigated in detail by using numerical simulation based on a diffusion equation. The simulation reveals that a very thick (>100 μm) epilayer is required for accurate measurement of carrier lifetimes if the bulk lifetime in the epilayer is longer than several micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
77
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 36 publications
3
77
1
Order By: Relevance
“…A carrier lifetime of 8.2 µs, which may be compared with 3C-SiC grown on silicon in which the carrier lifetime is ranging from a few to 120 nanoseconds, was reported [12]. The typical lifetime in as-grown 4H-SiC is around 1 μs under the low injection level, while higher values was reported to be enhanced from 0.69 to 9.5 μs after thermal treatment [13] or from 3.5 to 18-19 µs post carbon-implantation and annealing [14]. Thus a growth process that reproducibly maintains such quality could open up 3C-SiC for electronic and optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…A carrier lifetime of 8.2 µs, which may be compared with 3C-SiC grown on silicon in which the carrier lifetime is ranging from a few to 120 nanoseconds, was reported [12]. The typical lifetime in as-grown 4H-SiC is around 1 μs under the low injection level, while higher values was reported to be enhanced from 0.69 to 9.5 μs after thermal treatment [13] or from 3.5 to 18-19 µs post carbon-implantation and annealing [14]. Thus a growth process that reproducibly maintains such quality could open up 3C-SiC for electronic and optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…This measured carrier lifetime in as-grown 3C-SiC is much higher than the reported values in 3C-SiC grown by other methods, [19][20][21] even a little bit higher than the typical values in as-grown 4H-SiC. [11][12][13][14][15] The maximum carrier lifetime reported in asgrown 4H-SiC is 8.6 ls, 11 which was measured by l-PCD in a high-quality 50 lm thick CVD epilayer under an injection of 5 Â 10 12 cm À2 . The measured conditions are quite similar to our measurements.…”
mentioning
confidence: 39%
“…[11][12][13][14] Recently, it was shown that the reduction of the defects of Z 1/2 and EH 6/7 by post-growth processes results in an improvement of carrier lifetime. Kimoto et al 15 reported that the carrier lifetime in a 148-lm-thick 4H-SiC layer is enhanced from 0.69 to 9.5 ls after thermal treatment. Miyazawa et al 17 showed that using post carbon-implantation and annealing, the carrier lifetime in 4H-SiC was improved from 3.5 ls to an extraordinarily long value of 18-19 ls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second factor is the lack of drift/diffusion and surface recombination in the simulation, which would reduce the effective simulated lifetime up to several times for high lifetime samples. 21 None of these factors however would change the shown trend for samples from cells S1, S2 and C2. all samples and their measured lifetimes (and slightly below that of highest lifetime samples grown in cell S1), RB1 appears in large concentrations with a trend anti-proportional to τ meas and is the dominant recombination center in low-lifetime samples.…”
Section: Resultsmentioning
confidence: 99%